Ethnic differences in intrahepatic lipid and its association with hepatic insulin sensitivity and insulin clearance between men of black and white ethnicity with early type 2 diabetes. Issue 9 (18th June 2019) - Hakim, Olah; Bello, Oluwatoyosi; Bonadonna, Riccardo C.; Mohandas, Cynthia; Shojaee‐Moradie, Fariba; Jackson, Nicola; Boselli, Linda; Whitcher, Brandon; Shuaib, Haris; Alberti, Kurt George M. M.; Peacock, Janet L.; Umpleby, Anne Margot; et al.
Abstract: Intrahepatic lipid (IHL) is linked with reduced hepatic insulin sensitivity and insulin clearance. Despite their high risk for type 2 diabetes (T2D), there have been limited investigations of these relationships in black populations. We investigated these relationships in 18 white European (WE) and 18 black West African (BWA) men with T2D <5 years. They underwent magnetic resonance imaging to quantify IHL, a hyperinsulinemic euglycaemic clamp with [6, 6 2 H2 ] glucose infusion to assess hepatic insulin sensitivity and a hyperglycaemic clamp to assess insulin clearance. BWA men had lower IHL than WE men (3.7 [5.3] vs 6.6 [10.6]%, P = 0.03). IHL was inversely associated with basal hepatic insulin sensitivity in WE but not BWA men (BWA: r = −0.01, P = 0.96; WE: r = −0.72, P = 0.006) with a significant interaction by ethnicity ( P interaction = 0.05); however, IHL was not associated with % suppression of endogenous glucose production by insulin in either ethnicity. IHL showed a trend to an association with insulin clearance in BWA only (BWA: r = −0.42, P = 0.09; WE: r = −0.14, P = 0.58). The lack of association between IHL and hepatic insulin sensitivity in BWA men indicates IHL may play a lesser detrimental role in T2D in BWA men.